The Use of Content Words in the Dialogues of Comic Teasing Master (Former) Takagi-san - Feri Diki Arfendo; Yatno Yatno (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2021)
Content words contribute the meaning in sentences and comic is used to provide information, consolation, and education. The purpose of this study is to find out the types of content words and the use of content words in the dialogue of comic Teasing Master (former) Takagi-san. A total of 26 dialogues were extracted from 14th chapter in comic Teasing Master (former) Takagi-san. The method used in this study is lexical semantic approach and data collection method is documentation. The first result show for the types of content such as Verb (21) and Noun (18) are the most dominant content words, followed by Adverb (12) and Adjective (6). The second result show for the use of content words such as Noun: Subject (3), Object (10), Interjection (3), Gerund (1), Idiom (1). Verb: Simple Present (11), Progressive tense (4), Simple Past (2), Present Perfect (2), Past Perfect (1), Past Future Perfect (1). Adverb: Modify verb (7), Modify Sentence (2), Modify Adjective (3). Adjective: describe the quality of subject (3),Describe object (3). This research will be helpful for other researcher whoever will make study about semantic especially in content words.